2015
DOI: 10.1038/leu.2015.279
|View full text |Cite
|
Sign up to set email alerts
|

Search for familial clustering of multiple myeloma with any cancer

Abstract: Multiple myeloma (MM) is a disease of immunoglobulin-producing plasma cells, which reside mainly in the bone marrow. Family members of MM patients are at a risk of MM, but whether other malignancies are in excess in family members is not established and is the aim of this study. MM patients (24 137) were identified from the Swedish Cancer Registry from years 1958 to 2012. Relative risks (RRs) were calculated for MM defined by any cancer diagnosed in first-degree relatives and compared with individuals whose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
(30 reference statements)
4
29
0
Order By: Relevance
“…The RR of PCa in Swedish BRCA2 mutation carriers was reported to be only 2.3 [8]. In previous studies investigating familial risks between pairs of cancers, weak associations of PCa with breast cancer and myeloma were reported [3,9]. Family studies from Iceland detected associations of kidney cancer and melanoma with PCa [10].…”
Section: [ ( F I G _ 1 ) T D $ F I G ]mentioning
confidence: 99%
“…The RR of PCa in Swedish BRCA2 mutation carriers was reported to be only 2.3 [8]. In previous studies investigating familial risks between pairs of cancers, weak associations of PCa with breast cancer and myeloma were reported [3,9]. Family studies from Iceland detected associations of kidney cancer and melanoma with PCa [10].…”
Section: [ ( F I G _ 1 ) T D $ F I G ]mentioning
confidence: 99%
“…6,7 In the 2000s, systematic family studies, including in population-based registries, confirmed that first-degree relatives of patients with MM and its precursor condition, monoclonal gammopathy of unknown significance, have 2 to 4 times higher risk for MM, [8][9][10][11][12][13] and a higher risk for lymphomas and certain solid tumors. 14,15 According to estimates based on Swedish nationwide registries, about 2.4% of MM cases have a first-degree relative with MM. 14 Recently, genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) at 16 independent loci associated with MM risk.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 According to estimates based on Swedish nationwide registries, about 2.4% of MM cases have a first-degree relative with MM. 14 Recently, genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) at 16 independent loci associated with MM risk. [16][17][18][19] Although the discovery of risk alleles proves the existence of inherited susceptibility, the genetic background of familial MM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The highest overall RRs for SPC after NHL were associated with small lymphocytic, mantle cell and marginal zone lymphoma with the smallest effect being shown in respect of Burkitt lymphoma; these risks were approximately correlated with known survival for these subtypes, and hence good survival increases the life‐time chance for a SPC. Myeloma risk was high only after lymphoplasmacytic lymphoma (Waldenstrom) which could be predicted from the known familial association between the two diseases; consistently, lymphoplasmacytic lymphoma was also increased as SPC after myeloma. Other types of unique findings included anal cancer with a high risk after follicular lymphoma, high risk of leukemia after mantle cell and Burkitt lymphoma and high risk of kidney cancer after cutaneous and anaplastic T‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 94%